Reversible Vitamin B12 Deficiency Presenting with Acute Dementia, Paraparesis, and Normal Hemoglobin - Hani Almoallim; Fahtima S. Mehdawi; Mohammed M. Cheikh; Fahmi Al-dhaheri; Abdullah Mahir Aqeel (Case Reports in Neurological Medicine)
Vitamin B12 is essential for neurological function and its deficiency is associated with many neuropsychiatric disorders. We report the case of a previously healthy 53-year-old male patient presenting with delirium and multiple neurological findings. Complete blood analysis indicated megaloblastic anemia. All infectious causes were excluded owing to negative cultures (blood and urine). Tests for human immunodeficiency virus, syphilis, and toxoplasma were also negative. Metabolic workup showed severe vitamin B12 deficiency, decreased reticulocyte count, and increased direct bilirubin and lactate dehydrogenase. Intramuscular injection of cobalamin was started, and the patient showed significant improvement.